2018
DOI: 10.5812/semj.65797
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of Patients with Chronic Diseases to Use Health Information Technology: An Experience of a Developing Country

Abstract: Background: Nowadays, many health information technology (HIT) interventions are developed for self-care management of chronic diseases. Application of these interventions requires patients' readiness to use HIT. The current study aimed at determining the readiness of patients with chronic diseases referring to the clinics of educational hospitals in Khorramabad, Iran, to use HIT. Methods: The current cross sectional study was conducted on patients with chronic diseases referring to the clinics of teaching hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
3
3
1
Order By: Relevance
“…Comparison of the averages of charter domains revealed that the highest average was related to the right to access services, significantly surpassing the moderate level. This finding aligns with some previous studies ( 11 , 13 , 18 ). However, it contrasts with a study by Ranjbar et al, where the lowest average was found for this domain ( 19 ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Comparison of the averages of charter domains revealed that the highest average was related to the right to access services, significantly surpassing the moderate level. This finding aligns with some previous studies ( 11 , 13 , 18 ). However, it contrasts with a study by Ranjbar et al, where the lowest average was found for this domain ( 19 ).…”
Section: Discussionsupporting
confidence: 94%
“…The right to data confidentiality covered areas such access to patients’ medical records and avoiding disclosure of patients’ confidential information. In the present study, about half of the students had adequate awareness about this domain, consistent with the results of a similar study by Samadbeik et al ( 13 ). However, the students’ awareness of this domain was below average in a study by Mortazavi et al In this study, the poor awareness of rehabilitation science students was attributed to factors such as a lack of knowledge about the concept of privacy in rehabilitation treatments, which was related to the absence of effective education on the concepts of privacy and confidentiality in this group of students ( 11 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations